Safety and efficacy evaluation of halicin as an effective drug for inhibiting intestinal infections - Zhang, Maolu; Lin, Shuqian; Han, Lianquan; Zhang, Jiaming; Liu, Shaoning; Yang, Xiuzhen; Wang, Ruiming; Yang, Xiaohui; Yi, Yunpeng (Frontiers in Pharmacology, 2024)
Halicin, the first antibacterial agent discovered by artificial intelligence, exerts broad-spectrum antibacterial effects and has a unique structure. Our study found that halicin had a good inhibitory effect on clinical isolates of drug-resistant strains and Clostridium perfringens (C. perfringens). The safety of halicin was evaluated by acute oral toxicity, genotoxicity and subchronic toxicity studies. The results of acute toxicity test indicated that halicin, as a low-toxicity compound, had an LD50 of 2018.3 mg/kg. The results of sperm malformation, bone marrow chromosome aberration and cell micronucleus tests showed that halicin had no obvious genotoxicity. However, the results of the 90-day subchronic toxicity test indicated that the test rats exhibited weight loss and slight renal inflammation at a high dose of 201.8 mg/kg. Teratogenicity of zebrafish embryos showed that halicin had no significant teratogenicity. Analysis of intestinal microbiota showed that halicin had a significant effect on the intestinal microbial composition, but caused a faster recovery. Furthermore, drug metabolism experiments showed that halicin was poorly absorbed and quickly eliminated in vivo. Our study found that halicin had a good therapeutic effect on intestinal infection model of C. perfringens. These results show the feasibility of developing oral halicin as a clinical candidate drug for treating intestinal infections.